PELATIHAN DIGITAL MARKETING, TEKNIK FOTO PRODUK DAN PENGOLAHAN MINYAK JELANTAH DI DUKUH SRUMBUNG, KALURAHAN SEGOROYOSO, KECAMATAN PLERET, KABUPATEN BANTUL, DIY - Maelana, Herman Wahyu Dwi; Wijayanti, Irine Diana Sari; Murdapa, Purnama Andri; Purwanta, Purwanta; Wahyudiyono, Wahyudiyono (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2023)
Digital marketing training, product photo techniques and processing used cooking oil into candles are appropriate training in accordance with the times and the use of waste that can be further utilized. The purpose of this activity is to explain how to cultivate a creative, innovative, and independent entrepreneurial spirit through training on Digital Marketing, how to do product photos to make them attractive and used cooking oil waste treatment to create new products that can increase residents' income. This activity was held in Srumbung, Kalurahan Segoroyosot, Kapanewon Pleret, Kabupaten Bantul, DIY and was attended by the surrounding community. This activity is carried out by lecture and practice methods. Through lectures and practice activities, the community can understand the material presented and can practice directly. The community is active and responsive in this service activity.